Conceptual Model for Bomb Victims Information System (BVIS) In Iraq Using WAP Standard - Injas, Hasseeb Dawood (2012)
Many Iraqis have died resulting from insurgent bombings, revenge killings and U.S. military intervention during the 2003 invasion. This situation led to the destabilization of the security in the country and increased the number of dead and missing, making the search for missing loved ones very complex. To find a missing person, many procedures needed to be satisfied, one of which is to search in the area of bomb explosion, in the casualties section of the hospitals and in the police stations. Moreover, the Iraqis who are killed by terrorists are published in the newspapers but they do not account for all the victims and their information are imprecise. Wireless Application Protocol (WAP) is a technology that may provide the solution to problem of looking for loved ones. WAP is characterized as easy, fast delivery of relevant information and services to mobile users. It is a secure technology allowing users to access instant information through wireless handheld devices like mobile phones, pagers, two-way radios, smart phones and communications. The goal of the present study is to develop a conceptual design model of Bomb Victims Information System (BVIS) through the use of WAP Standard to provide information regarding Iraqi bomb victims.